2018
DOI: 10.1155/2018/5215868
|View full text |Cite
|
Sign up to set email alerts
|

Association between Sleep Apnea Hypopnea Syndrome and the Risk of Atrial Fibrillation: A Meta-Analysis of Cohort Study

Abstract: Numerous reports have been done to seek the relationship between sleep apnea hypopnea syndrome (SAHS) and the risk of atrial fibrillation (AF). However, definite conclusion has not yet been fully established. We examined whether SAHS increases AF incidence in common population and summarized all existing studies in a meta-analysis. We summarized the current studies by searching related database for potential papers of the association between SAHS and the risk of AF. Studies that reported original data or relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 35 publications
0
22
0
4
Order By: Relevance
“…The presence of OSA increases the risk of developing AF with a relative risk of 1.7, as found by a recent meta -analysis. 61 Multiple observational studies have suggested that CPAP treatment may lower the rate of AF recurrence following electrical cardioversion, 58 though data from RCTs are lacking. Interestingly, symptomatology characteristic of OSA is less predictive in this population than in the general OSA population.…”
Section: Coronary Artery Disease / Ischemic Heart Diseasementioning
confidence: 99%
“…The presence of OSA increases the risk of developing AF with a relative risk of 1.7, as found by a recent meta -analysis. 61 Multiple observational studies have suggested that CPAP treatment may lower the rate of AF recurrence following electrical cardioversion, 58 though data from RCTs are lacking. Interestingly, symptomatology characteristic of OSA is less predictive in this population than in the general OSA population.…”
Section: Coronary Artery Disease / Ischemic Heart Diseasementioning
confidence: 99%
“…A recent meta-analysis of 8 cohort studies showed that the presence of OSA increases the risk of developing AF with a RR of 1.70 (95% CI, 1.53-1.89) (46). This appeared to occur in a dose dependent fashion: RR 1.52 (95% CI, 1.28-1.…”
Section: Incident Afmentioning
confidence: 99%
“…This appeared to occur in a dose dependent fashion: RR 1.52 (95% CI, 1.28-1. (46). In a retrospective cohort study of 3,452 adults who had sleep studies, independent predictors of incident AF in subjects <65 years were known risk factors such as age, male gender, CAD and BMI but also the presence of nocturnal hypoxia, the latter increasing the risk of incident AF threefold after correcting for obesity (47).…”
Section: Incident Afmentioning
confidence: 99%
“…In most of the conducted studies, a significant association has been observed between sleep disorders and AF risk (RR range of 1.26-2.51) [85]. A recent meta-analysis reported that sleep disorders increased the risk of AF significantly (RR = 1.70), and higher severity of sleep disorders was associated with a higher AF risk [86]. Moreover, another meta-analysis confirmed that the risk of AF was greater among patients with sleep disorders compared with the control group OR (Olds ratio) = 2.1 [87].…”
Section: Sleep Disordersmentioning
confidence: 99%